FINANCIAL SUSTAINABILITY OF HIGHER EDUCATION INSTITUTIONS - Kuzmina, Jekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Since the beginning of the XXI century, there have been clear modifications in the sector of higher education, when the institutions have moved near to the economic sector. These changes were primary introduced as the consecutive response to the transformation processes within the society, which should be embedded in the following construct: there was a clear move towards a more competitive and market-based system. Due to the changes in the operating environment financial sustainability and its management for the higher education institutions became one of the core elements. The main objective of the current paper is to discuss the practical application of the methodology for the management of higher education institutions based on the example of Latvian private higher education institutions. The author would like to argue that the paper contributes to the fundamental discussion of financial sustainability in the field of higher education institution management. Moreover, it has got practical implications for the management of the organizations not only in Latvia but also in other countries when efficiency and effectiveness are primary issues.